ATP‐induced cellular stress and mitochondrial toxicity in cells expressing purinergic P2X7 receptor. Issue 2 (12th March 2015) - Seeland, Swen; Kettiger, Hélène; Murphy, Mark; Treiber, Alexander; Giller, Jasmin; Kiss, Andrea; Sube, Romain; Krähenbühl, Stephan; Hafner, Mathias; Huwyler, Jörg
Abstract: Under pathological conditions, the purinergic P2X7 receptor is activated by elevated concentrations of extracellular ATP. Thereby, the receptor forms a slowly dilating pore, allowing cations and, upon prolonged stimulation, large molecules to enter the cell. This process has a strong impact on cell signaling, metabolism, and viability. This study aimed to establish a link between gradual P2X7 activation and pharmacological endpoints including oxidative stress, hydrogen peroxide generation, and cytotoxicity. Mechanisms of cellular stress and cytotoxicity were studied in P2X7‐transfected HEK293 cells. We performed real‐time monitoring of metabolic and respiratory activity of cells expressing the P2X7‐receptor protein using a cytosensor system. Agonistic effects were monitored using exogenously applied ATP or the stable analogue BzATP. Oxidative stress induced by ATP or BzATP in target cells was monitored by hydrogen peroxide release in human mononuclear blood cells. P2X7‐receptor activation was studied by patch‐clamp experiments using a primary mouse microglia cell line. Stimulation of the P2X7 receptor leads to ion influx, metabolic activation of target cells, and ultimately cytotoxicity. Conversion of the P2X7 receptor from a small cation channel to a large pore occurring under prolonged stimulation can be monitored in real time covering a time frame of milliseconds to hours. Selectivity of the effects can be demonstrated using the selective P2X7‐receptor antagonist AZD9056. Our findings established a direct link between P2X7‐receptor activation by extracellular ATP or BzATP and cellular events culminating in cytotoxicity. Mechanisms of toxicity include metabolic and oxidative stress, increase in intracellular calcium concentration and disturbance of mitochondrial membrane potential. Mitochondrial toxicity is suggested to be a key event leading to cell death. Abstract : e00123